Real World Learning in Outdoor Environmental Education Programs The Practice from the Perspective of Educational Research - Činčera, Jan (Masaryk University Press, 2021)
Title in English: Učení v opravdovém světě ve venkovních programech environmentální výchovy: Praxe z pohledu pedagogického výzkumu This book analyzes the theoretical frameworks shaping the practice of outdoor environmental education programs. For the analyses, the authors applied the Real World Learning Model that defines the quality criteria for this kind of practice. They also further examined the Model from the perspectives of relevant theory and research, as well as from the perspectives of program leaders, accompanying teachers, and participating students. Specifically, the authors selected five programs, all three to five days long, offered by Czech outdoor environmental education centers for students in the 3rd to 7th grades and focused on shaping students' environmental values and behavior.